2015
DOI: 10.1111/cup.12479
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytic tumors with intraepidermal melanophages: a report of five cases with review of 231 archived cutaneous melanocytic tumors

Abstract: Dermal melanophages are frequently encountered in both benign melanocytic nevi and malignant melanoma. In contrast, intraepidermal melanophages (IEM) are under-recognized in melanocytic lesions and their biologic significance is not understood. Herein, we report the clinical and histopathologic features of five melanocytic lesions featuring IEM encountered prospectively in our dermatopathology practice at the University of Chicago. Two hundred and thirty-one (231) archived skin primary melanocytic proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…On the contrary, melanin pigment has also been found in dermal tissue of SL lesions, and it has been reported that the majority of melanin pigment in the dermis is localized on CD163 and FXIIIa positive macrophages 12,13 . These melanin‐phagocytosing macrophages are termed melanophages and are also known to be frequently present in benign melanocytic nevi and malignant melanomas, 14 but detailed studies have not been conducted. Recent in vitro studies have reported the phenomenon of melanin uptake by dermal fibroblasts, 15 raising the possibility that cells other than macrophages may be taking up melanin in the dermis of SL lesions.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, melanin pigment has also been found in dermal tissue of SL lesions, and it has been reported that the majority of melanin pigment in the dermis is localized on CD163 and FXIIIa positive macrophages 12,13 . These melanin‐phagocytosing macrophages are termed melanophages and are also known to be frequently present in benign melanocytic nevi and malignant melanomas, 14 but detailed studies have not been conducted. Recent in vitro studies have reported the phenomenon of melanin uptake by dermal fibroblasts, 15 raising the possibility that cells other than macrophages may be taking up melanin in the dermis of SL lesions.…”
Section: Introductionmentioning
confidence: 99%